2009
DOI: 10.1258/jms.2009.008062
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to undergo colorectal cancer screening in first-degree relatives of hospitalized patients with colorectal cancer

Abstract: Aims To evaluate whether willingness to undergo colonoscopy screening is influenced by being a first-degree relative of hospitalized patients with or without colorectal cancer after briefing and surgeon recommendation. Methods We performed a cross-sectional study of 327 first-degree relatives of hospitalized patients aged higher than 40 years, divided into Group A (151 relatives of colorectal cancer patients) and Group B (176 relatives of non-cancer patients) at the University Hospital of the Canary Islands, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
2
2
1
Order By: Relevance
“…30,31 Many studies found that positive family history of colorectal cancer as a motivational factor to undergo cancer screening test. 32,33 Interestingly, a large percentage (71%) of the studied population (368/521) willing to take the screening test even without any apparent symptoms which is consistent with previous studies conducted among Saudi general population. 34,35 Such positive attitude indicates that the studied populations are ready and willing to participate in future colorectal cancer screening program.…”
Section: Discussionsupporting
confidence: 87%
“…30,31 Many studies found that positive family history of colorectal cancer as a motivational factor to undergo cancer screening test. 32,33 Interestingly, a large percentage (71%) of the studied population (368/521) willing to take the screening test even without any apparent symptoms which is consistent with previous studies conducted among Saudi general population. 34,35 Such positive attitude indicates that the studied populations are ready and willing to participate in future colorectal cancer screening program.…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed that 56.1% of FDRs who qualified for screening colonoscopy due to their age underwent a screening colonoscopy. This rate correlates with data from the literature (29-67%), but is in the upper range [1,5,8,19,26,27]. Stock and Brenner [28] showed prevalences of lower gastrointestinal endoscopy and fecal occult blood test utilization among adults aged 50 years or older in 11 countries (from the Survey of Health, Aging, and Retirement in Europe, SHARE).…”
Section: Discussionsupporting
confidence: 85%
“…The similarity of these data is an indication of its reliability. We found that a higher percentage of CRC patients were informed of their FDRs' increased CRC risk (80.6%) than in other studies (33-77.6%) [3,5,8,[19][20][21][22][23] Several factors might have influenced the high rate of informed CRC patients in our study. First, the flow of information is better in young index patients with CRC and in conditions with strong family togetherness [3,24,25].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Despite the evidence that physician recommendation to screen has a powerful motivating effect on CRC screening uptake, [58] FDRs are most often not informed by physicians about the need for CRC screening [59]. A significantly higher rate of colonoscopy screening can result among those siblings where the index cases were aware of their FDRs’ increased risk [27].…”
Section: Discussionmentioning
confidence: 99%